2020
DOI: 10.1039/d0tb00508h
|View full text |Cite
|
Sign up to set email alerts
|

A fiber-shaped neural probe with alterable elastic moduli for direct implantation and stable electronic–brain interfaces

Abstract: A fiber-shaped neural probe with alterable elastic moduli allows direct implantation and enables adaptive electronic–tissue interfaces post implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…Astrocytes, immune-reactive cells labeled by glial fibrillary acidic protein (GFAP), were shown to be populated more densely near the silica fiber implant than the OWHF implant (Fig. 5 g and i), indicating that the silica fiber implant triggered a more severe immune response than the OWHF implant [ 6 , 45 ]. In the OWHF - implanted cortical tissue, IgG, a common serum antibody in blood circulation [ 46 ], was restricted to the vasculature and removed upon perfusion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes, immune-reactive cells labeled by glial fibrillary acidic protein (GFAP), were shown to be populated more densely near the silica fiber implant than the OWHF implant (Fig. 5 g and i), indicating that the silica fiber implant triggered a more severe immune response than the OWHF implant [ 6 , 45 ]. In the OWHF - implanted cortical tissue, IgG, a common serum antibody in blood circulation [ 46 ], was restricted to the vasculature and removed upon perfusion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The authors then suggested the use of CFs as an alternative shuttle device as a means to reduce the insertion footprint. In a more recent study reported by Tang et al (2020), the authors functionalized CNT fibers with a layer of calcium ion crosslinked sodium alginate. The functionalized fiber electrodes are rigid before implantation but become softer after insertion.…”
Section: Carbon Nanotube (Cnt)-based Fibersmentioning
confidence: 99%
“…[ 117 ] To further simplify the implantation process, a fiber electrode with alterable elastic moduli was developed (Figure 8A). [ 27 ] The electrode based on CNT fiber exhibited as rigid as metal wires to ensure facile and direct implantation and turned as soft as brain tissue after implantation to ensure dynamic and stable interfaces (Figure 8B). It delivered a stable neuron recording for 4 weeks in vivo.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…[ 19 ] “Neural probe.” Reproduced with permission: Copyright 2020, Royal Society of Chemistry. [ 27 ] “Wireless health detection.” Reproduced with permission: Copyright 2018, Wiley‐VCH [ 29 ]…”
Section: Introductionmentioning
confidence: 99%